2021
DOI: 10.2147/cmar.s316935
|View full text |Cite
|
Sign up to set email alerts
|

A Novel miRNA–mRNA Axis Involves in Regulating Transcriptional Disorders in Pancreatic Adenocarcinoma

Abstract: Background Currently, there is still a lack of understanding about the mechanism and therapeutic targets of pancreatic adenocarcinoma (PAAD). The potential of miRNA–mRNA networks for the identification of regulatory mechanisms involved in PAAD development remains unexplored. Methods We compared differentially expressed miRNAs (DEMIs) and differentially expressed genes (DEGs) in PAAD and normal tissues from the Gene Expression Omnibus (GEO) database. Transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The expression level of HOXC4 mRNA in tumor group was significantly higher than that in normal samples. HOXC4 is the target of miR-455-3p and its formation of miR-455-3p-HOXC4 axis may be closely related to the metastasis and prognosis of human pancreatic cancer ( Shang et al, 2021 ). GH1 participates in the formation of GIPC1, which is necessary for integrin circulation during cell migration, angiogenesis and cytokinesis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of HOXC4 mRNA in tumor group was significantly higher than that in normal samples. HOXC4 is the target of miR-455-3p and its formation of miR-455-3p-HOXC4 axis may be closely related to the metastasis and prognosis of human pancreatic cancer ( Shang et al, 2021 ). GH1 participates in the formation of GIPC1, which is necessary for integrin circulation during cell migration, angiogenesis and cytokinesis.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of FBXO45 facilitated the ubiquitination of IGF2BP1 and upregulation of PLK1, which conferred to liver tumorigenesis [30]. FBXO45 expression was high and associated with poor prognosis in pancreatic ductal adenocarcinoma (PDAC) [31,32]. Moreover, bioinformatics analysis showed that FBXO45 could be a potential oncogene in esophageal cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…This miRNA can impair HCC cell malignancy via suppression of insulin growth factor receptor expression, thereby disrupting glycolysis ( Hu et al, 2019 ; Jiang et al, 2019 ). Gao et al (2018) , Yang et al (2017) , and Shang et al (2021) reported that low expression of miR-455-3p in non-small-cell lung cancer, esophageal squamous cell carcinoma (ESCC), and pancreatic cancer (PAAD) tissues was strongly associated with poor prognosis. miR-455-3p acts as a tumor suppressor in esophageal squamous cell carcinoma (ESCC) and inhibits cell proliferation and invasion by targeting FAM83F.…”
Section: Discussionmentioning
confidence: 99%